2017
DOI: 10.1049/iet-map.2016.0112
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimisation of broadband stacked microstrip antennas using transmission line model

Abstract: This study presents a technique for analysis of multilayered stacked microstrip antennas using transmission‐line (TRL) equivalent circuits, which has been validated by analysis of a broadband stacked antenna. A circuit model is developed by dividing the antenna into a number of metal patch pairs which are modelled as TRLs. A procedure has also been outlined for applying the proposed method to a large class of multilayered stacked patch antennas. The proposed method models all the coupling parasitics of the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Generally most transmitting patch has square, rectangular, dipole, triangular, elliptical, and circular. Dielectric constants 2.2≤ ε r ≥ 12 is accessible for substrate [9][10]. Thickness of substrates assumes an essential part in antenna attributes by and large are in the range .03 ≤ L≥ 0.05 cm utilized as ground plane.…”
Section: Microstrip Patch Antennamentioning
confidence: 99%
“…Generally most transmitting patch has square, rectangular, dipole, triangular, elliptical, and circular. Dielectric constants 2.2≤ ε r ≥ 12 is accessible for substrate [9][10]. Thickness of substrates assumes an essential part in antenna attributes by and large are in the range .03 ≤ L≥ 0.05 cm utilized as ground plane.…”
Section: Microstrip Patch Antennamentioning
confidence: 99%
“…In order to minimize the cost, miniaturised size, and easy integration author Zahang et al (2016) [11] introduced a dual-frequency band polarisation method which achieves the radition about 7.0and 5.9 in the two bands. In Katyal et al (2016) [12], a transmissionline equivalent circut technique is presented for analysis of multilayered MsP antenna.The performance of the technique is validated by analysis of broadband antenna and found that the proposed method is capable for quick circuir level imitation and optimization. In the study of different type of printed antennas having different type of patch like, rectangular, square, triangular, circular, elliptical are suitable for 60HZ wairless application.…”
Section: Related Workmentioning
confidence: 99%
“…In the work of Katyal et al [12], a transmission-line equivalent circuit technique is presented for analysis of multilayered micro strip patch antennas (MPA). [13][14] has proposed a key sight technologies, this given technology is very helpful of radio frequency design.…”
Section: Related Workmentioning
confidence: 99%